vieira guimarães (1864-1939) e a arqueologia em tomar: uma abordagem sobre o território e as gentes - Martins, Ana Cristina (2020)
Born in Tomar in 1864, graduated in medicine from Escola Médico Cirúrgica de Lisboa, José Vieira Guimarães died in Lisbon in 1939. During his life performed several actions to enhance cultural heritage from Tomar. He had participated in archaeological projects, publications and contacted with scholars like the archaeologist José Leite de Vasconcelos. José Vieira Guimarães was involved in associations and academies, was a member of Association of Portuguese Archaeologists, had participated in excavations, investigated, published articles and books, participated in congresses, confirmed the hypothesis of Seilium romana being located in Tomar. We present unprecedented content about his participation in a congress in 1923, as well as, we consider that he had fault with the potential proof of his work.